LEVELS OF PROFESSIONAL PEDAGOGICAL ACTIVITY FUTURE MATHEMATICS TEACHER BASED ON INNOVATIVE TECHNOLOGIES FOR LEARNING (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article provides information on the level of professional pedagogical activity of a future mathematics teacher based on innovative teaching technologies, as well as on the quality of education .